Assessment of the failure rate of the stormwater drainage system in Lublin - Żmijan, Marta; Kowalski, Dariusz (Instal, 2025)
One of the main problems of operating storm water systems in cities is the issue of their ownership. In many cases, this infrastructure is managed by the municipality or the local road authority. In both cases, the owners often lack the capacity to carry out effective maintenance and operational activities. There are problems with systematic diagnostics and ongoing repairs. Additionally, stormwater management is hindered by fragmented responsibilities, insufficient funding, and a lack of integration with spatial planning and the management of stormwater receiving structures. The article presents the results of the research on the failure rate of the storm water system in Lublin, based on data collected by the local water and sewage company over the last 10 years. The analysis confirms the differentiation of the failure rates of the storm water and the sanitary sewer system in this city. The results obtained may be used in the future to determine standards enabling the classification of stormwater drainage systems into individual failure rate groups, similarly to the existing classes developed for water and sewage systems.